2001
DOI: 10.1046/j.1523-1755.2001.060002505.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel somatostatin analogue prevents early renal complications in the nonobese diabetic mouse

Abstract: GH antagonism by PTR-3173 has a blunting effect on renal/glomerular hypertrophy, albuminuria, and glomerular filtration rate (GFR) in diabetic NOD mice. This phenomenon is apparently associated with the prevention of renal IGF-I accumulation. Thus, modulation of GH effects may have beneficial therapeutic implications in diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 32 publications
1
25
1
Order By: Relevance
“…Further, as a novel finding we have demonstrated octreotide treatment to be effective in reducing renal and glomerular growth along with a reduction in GH hypersecretion and increased local kidney IGF-I levels. Similar effects were observed just recently in the NOD mouse using a novel somatostatin analogue (Landau et al 2001). This may provide further evidence for a significant role for GH and IGF-I in diabetic renal growth and morphological changes in experimental diabetes in mice as has previously been demonstrated in diabetic rats.…”
Section: Discussionsupporting
confidence: 85%
“…Further, as a novel finding we have demonstrated octreotide treatment to be effective in reducing renal and glomerular growth along with a reduction in GH hypersecretion and increased local kidney IGF-I levels. Similar effects were observed just recently in the NOD mouse using a novel somatostatin analogue (Landau et al 2001). This may provide further evidence for a significant role for GH and IGF-I in diabetic renal growth and morphological changes in experimental diabetes in mice as has previously been demonstrated in diabetic rats.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, we and others have previously shown that the inhibition of GH, either by the use of a GHR antagonist [7] or a somatostatin analogue, has protective renal effects in animals with type I DM [8]. In addition, GH administration to diabetic rats had adverse renal effects, such as worsening albuminuria and increased renal IGFBP1 levels, which, as mentioned, may increase the local trapping of IGF-I [9].…”
Section: Introductionmentioning
confidence: 90%
“…Lean heterozygous and nondiabetic db/N mice were used as controls. All animals were killed 4 weeks after the onset of diabetes mellitus, as previously described [11]. Body weight was measured twice weekly.…”
Section: Animal Experimentationmentioning
confidence: 99%
“…A subset of experiments was performed using a somatostatin analogue (PTR-313: Peptor, Rehovot, Israel) previously described by us as having protective effects on the kidney in a model of type 1 diabetes mellitus [11]. The agent was provided daily over 4 weeks by s.c. injections (1 mg kg −1 day −1 ) to diabetic animals, with control animals receiving the equivalent amount of saline.…”
Section: Animal Experimentationmentioning
confidence: 99%